2002
DOI: 10.1021/es015622e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Speciation and Toxicity of Nickel Species in Natural Waters from the Sudbury Area (Canada)

Abstract: Metal complexation properties of dissolved organic carbon (DOC) in freshwaters are recognized but poorly understood. Here, we investigated the release of free nickel from Ni-DOC complexes using nickel-polluted freshwaters from Sudbury (Canada). We used the Competing Ligand Exchange Method with Chelex-100 as the competing ligand to measure the rate of free Ni2+ ion released by the dissociation of Ni-DOC complexes. The kinetic studies showed that the fastest kinetically distinguishable component representing app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
24
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 25 publications
(19 reference statements)
6
24
1
Order By: Relevance
“…This is in line with the literature reports showing the toxic effects of nickel on microalgae at micromolar levels (Mandal et al 2002).…”
Section: Influence Of Nickel On Microalgae Growthsupporting
confidence: 93%
See 2 more Smart Citations
“…This is in line with the literature reports showing the toxic effects of nickel on microalgae at micromolar levels (Mandal et al 2002).…”
Section: Influence Of Nickel On Microalgae Growthsupporting
confidence: 93%
“…It has been previously reported that at micromolar levels nickel is toxic to a variety of algae, invertebrates, and fish (Mandal et al 2002;Nriagu 1980;Bielmyer et al 2006). Several studies exist on the toxicity of nickel to algae and on the bioconcentration of nickel by brown algae and by cyanobacteria and green algae (Wang and Wood 1984;Bordons and Jafre 1987;Wong et al 2000).…”
Section: Nickel Effects On Algaementioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [6][7] used to study Ni speciation. However, in these studies [8][9][10], no attempt was made to 65 measure equilibrium speciation, but information on the lability of the Ni-DOM complexes in 66 surface waters was derived from the rate of dissociation. Fractions of labile Ni in surface 67…”
mentioning
confidence: 99%
“…water were found to range from 20 to 80% [8], 40 to 100% [9] and 31 to 88% [10]. The labile 68 fractions are assumed to include free Ni 2+ ion, inorganic Ni complexes and small Ni-DOM 69 complexes that dissociate within the operational conditions.…”
mentioning
confidence: 99%